Determinants of postnatal care utilization in sub-Saharan Africa: a meta and multilevel analysis of data from 36 sub-Saharan countries - Zemenu Tadesse Tessema; Lake Yazachew; Getayeneh Antehunegn Tesema; Achamyeleh Birhanu Teshale (BMC, 2020)
Abstract Introduction Globally, over 65% of maternal deaths occur during the first 42 days of postpartum while the same proportion of neonatal deaths occur during the first 7 days of life. In sab- Saharan Africa, 4.7 million mothers, newborns, and children die on annual basis. As to our knowledge, there is no study on postnatal care utilization that incorporates all sub-Saharan Africa countries that had DHS data. Therefore, this study aimed at identifying pooled magnitude and determinants of postnatal care utilization in sub-Saharan Africa. Method A population-based cross-sectional study from the most recent Demographic and Health Surveys data from the period of 2006 to 2018 of 36 SSA countries were used. A total weighted sample of 286,255 reproductive-age women who gave birth 5 years preceding the survey were included in the study. A meta-analysis of DHS data of each Sub-Saharan countries was conducted to generate pooled magnitude and a forest plot was used to present it. A multilevel logistic regression model was fitted to identify determinants of postnatal care utilization. The AOR (Adjusted Odds Ratio) with their 95% CI and p-value ≤0.05 was used to declare that determinates associated with postnatal care utilization. Result The pooled magnitude of postnatal care utilization in sub-Saharan Africa countries was 52.48% [95% CI: 52.33, 52.63], with the highest postnatal care utilization in the Central Region of Africa (73.51%) and the low postnatal care utilization in Eastern Regions of Africa (31.71%). In the multilevel logistic regression model region, residence, age group, maternal education, maternal occupation, media exposure, ANC visit, place of delivery, and accessing health care were determinants of postnatal care utilization in Sub-Saharan Africa. Conclusion The coverage of postnatal care service utilization was low with high disparities among the region. Being in rural residence, young age group, low education level, had no occupation, not exposed to media, a big problem to access health care, not had ANC visit, and home delivery was associated with low postnatal care service utilization. This study evidenced that there is a wide gap in postnatal care utilization between SSA countries. Special attention is required to improve health accessibility, utilization, and quality of maternal health services to increase postnatal care service utilization in the region.